1991
DOI: 10.1111/j.1469-8986.1991.tb00731.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Isoproterenol on T‐Wave Amplitude and Heart Rate: A Dose‐Response Study

Abstract: This report examines the hypothesis that electrocardiographic T-wave amplitude is sensitive to graded increases in beta-sympathetic stimulation of the heart. Beta-adrenergic activity was manipulated pharmacologically in 9 healthy men by bolus infusion of isoproterenol in each of six doses: 0.1, 0.25, 0.5, 1.0, 2.0, and 4.0 micrograms. Results indicated that elevations in heart rate above placebo values increased as a linear function of isoproterenol dose. In contrast, the dose-response curve for T-wave amplitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
16
0

Year Published

1992
1992
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 19 publications
1
16
0
Order By: Relevance
“…One recent report [21] showed that elevations in heart rate above placebo values increased as a linear function of isoproterenol dose. In contrast, the dose-response curve for T-wave amplitude was best described by a quadratic function: an initial reduction in T-wave amplitude at low levels of isoproterenol infusion was followed by a significant reversal of this effect at higher doses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One recent report [21] showed that elevations in heart rate above placebo values increased as a linear function of isoproterenol dose. In contrast, the dose-response curve for T-wave amplitude was best described by a quadratic function: an initial reduction in T-wave amplitude at low levels of isoproterenol infusion was followed by a significant reversal of this effect at higher doses.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies suggest a complex relationship between T wave amplitude and the effects of isoproterenol and other adrenergic agents [21,22] . These studies did not examine the effects of isoproterenol on T wave amplitude variability.…”
mentioning
confidence: 99%
“…This involves the graded administration of isoproterenol, a non selective beta adrenergic agonist (Arnold & McDevitt, 1983; Cleaveland, Rangno, & Shand, 1972; Contrada, Dimsdale, Levy, & Weiss, 1991; George, Conolly, Fenyvesi, Briant, & Dollery, 1972; Martinsson, Lindvall, Melcher, & Hjemdahl, 1989; Mills, Dimsdale, Ancoli-Israel, Clausen, & Loredo, 1998; Yu, Kang, Ziegler, Mills, & Dimsdale, 2007). When administered intravenously, isoproterenol primarily results in rapid elevations in heart rate and contractility, relaxation of bronchial smooth muscle, and reductions in diastolic blood pressure.…”
Section: Introductionmentioning
confidence: 99%
“…In humans, TWA decrease was seen after subcutaneous or intramuscular administration of epinephrine (Hartwell, Burrett, Graybiel, & White, 1942;Katz, Hamburger, & Lev, 1932;Levine, Ernstene, & Jacobson, 1930), and after administration of a nonselective b-agonist (isoproteronol; Contrada et al, 1989;Contrada, Dimsdale, Levy, & Weiss, 1991).…”
mentioning
confidence: 99%
“…Dauchot and Gravenstein (1971) and Annila, Yli-Hankala, and Lindgren (1993) indeed found that an acetylcholinergic antagonist (atropine) led to a decrease in the TWA. Contrada et al (1989Contrada et al ( , 1991 further reported a sudden paradoxical TWA increase during very high doses of isoproterenol infusion and reasoned that (baroreflex-induced) increases in vagal activity might have caused the increase in the TWA. These findings suggest that changes in cardiac vagal activity also affect the TWA, which would invalidate it as a pure SNS measure.…”
mentioning
confidence: 99%